Air and PCM cooling for battery thermal management considering battery cycle life. (5th June 2020) - Chen, Fenfang; Huang, Rui; Wang, Chongming; Yu, Xiaoli; Liu, Huijun; Wu, Qichao; Qian, Keyu; Bhagat, Rohit
Highlights: Performance of air and PCM battery cooling is studied. Realistic charge/discharge current profile is applied in simulations. Battery non-uniform degradation and battery cycle life are analysed. A performance index for assessment of battery thermal management system is proposed. Abstract: Cycle life of lithium-ion batteries (LIBs) is essential for the application of hybrid electric vehicles (HEV) and electric vehicles (EV). Since temperature greatly affects degradation rate and safety of LIBs, battery thermal management system (BTMS) is required. In this paper, the performance of active air cooling and passive phase change material (PCM) cooling for BTMS are assessed in terms of battery thermal states and cycle life. A coupled one-dimensional electrochemical and two-dimensional thermal models are developed to simulate the temperature of a battery module with 16 cylindrical (26650) graphite-LiFePO4 lithium-ion battery cells. The model is validated with the experimental data taken from literature. By applying a realistic current profile of a HEV to the battery model, simulations are performed at various ambient temperatures, inlet velocities of air cooling and PCM phase change temperatures. The battery cycle life and its non-uniformity across the module are estimated with a battery degradation model with inputs of battery temperature results. The study shows that active air cooling has a better cooling effect than PCM cooling, especially at high ambient temperatures. But the active air cooling leads to a large temperature non-uniformity at low inlet air velocities. The cycle life of the battery module under air cooling is longer than that of PCM cooling, although a larger life non-uniformity is observed. Furthermore, two methods are compared by a newly proposed evaluation index called cyclical cost. This index considers both the battery cycle life and the parasitic power consumption of the BTMS. The result demonstrates that air cooling has a lower cyclical cost than PCM cooling. When the inlet velocity of the air cooling system increases, the cyclical cost has a trend of decreasing first and then increasing. This paper provides a guide for the development of BTMS to further prolong the cycle life and reduce total operating cost of LIBs.